Handbook of hydraulics for the solution of hydraulic engineering problems - Brater, Ernest Federick (McGraw-Hill, 1996)
Your one-stop answer guide to hydraulics engineering and design. Turn to Handbook of Hydraulics, Seventh Edition, for the tables, formulas, computer applications, and other resources you need to design and engineer virtually any hydraulic system. Bringing Ernest F. Brater and Horace W. King's last edition into the 21st century, James E. Lindell and C.Y. Wei have revised and updated this unmatched advisor--coverting all constants to metric units--to give you powerful solutions governing: Viscosity, surface tension, and elasticity; fluid pressures and hydraulic forces; laminar, turbulent, steady, and unsteady flows; oscillatory, breaking, and wind-generated waves plus shore erosion control' flow through orifice gates, tubes, weirs, and pipes; uniform and nonuniform flow in open channels; high-velocity transitions through straight-walled, enlargement, and curved-wall constrictions; unsteady open channel and spatially variable flow; flow measurement with meters, pilot tubes, venture flumes, and other devices; computer-based numerical methods; much more.